Integrative approach for diabetic foot management– a case report - Neelambika, G.B. (J Ayurveda Integr Med, 2018)
Non-healing diabetic foot has always demanded more attention from the surgeon due to the distinct problem it possesses. There is a constant need for the evolvement in the management and this case is one such attempt. A 62-year-old male patient with a history of diabetes mellitus since 10 years presented with a non-healing foot ulcer since 1 month. He was managed with Ayurveda internal and external interventions for dusta vrana combined with contemporary methods like vacuum assisted wound suction and skin grafting. The patient who presented with non-healing diabetic foot was found to have better wound healing with combined intervention. The current approach indicates the better outcome with multi-dimensional approach towards diabetic foot.